The Potential of Constructed Wetlands for Liquid Waste Management in Small and Medium-Scale Tannery: A Literature Review - Febriani Purba (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2021)
The leather tanning industry or tannery, mainly in the small and medium scale (SMEs), is not environmentally friendly. Limited capitals drive the SMEs-scale tanneries to dispose of liquid waste directly into water bodies without proper treatment. It might cause serious environmental problems due to the high content of COD, BOD, chromium, and dyes. Treatment of liquid waste using constructed wetlands has been widely used because it is efficient, cheap, and powerful. This review discusses the latest studies in the wastewater treatment of tanneries using phytoremediation techniques and constructed wetlands and their potential applications in the SMEs tanneries.